2013
DOI: 10.1176/appi.ps.000802012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Great East Japan Earthquake on Caregiver Burden: A Cross-Sectional Study

Abstract: A statistically significant difference in emotional stress was observed among caregivers who were forced to evacuate after the earthquake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Following the 2011 earthquake and nuclear disaster, reduction in the number of medical personnel, including nurses, has been reported in disaster-affected areas. 12 In a survey targeting nurses working at a university hospital, conducted 2 years after the disaster, a large number of nurses had considered leaving their jobs because of “anxiety about life after the accident,” “possible radiation health effects in children,” and “anxiety about relationships with colleagues in the hospital.” 13 Few studies have reported that the work of public health nurses or caregivers can be highly stressful compared with that of the general population 14,15 ; however, no study has specifically focused on the mental health of hospital nurses and how differences in radiation knowledge, risk perceptions, or other stress-related aspects influence their mental health. Furthermore, there is no report regarding coping strategies for their mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Following the 2011 earthquake and nuclear disaster, reduction in the number of medical personnel, including nurses, has been reported in disaster-affected areas. 12 In a survey targeting nurses working at a university hospital, conducted 2 years after the disaster, a large number of nurses had considered leaving their jobs because of “anxiety about life after the accident,” “possible radiation health effects in children,” and “anxiety about relationships with colleagues in the hospital.” 13 Few studies have reported that the work of public health nurses or caregivers can be highly stressful compared with that of the general population 14,15 ; however, no study has specifically focused on the mental health of hospital nurses and how differences in radiation knowledge, risk perceptions, or other stress-related aspects influence their mental health. Furthermore, there is no report regarding coping strategies for their mental health.…”
Section: Introductionmentioning
confidence: 99%
“…WHO reported that mental, psychological and central nervous system effects following the Chernobyl accident were due to the mental stress from fear of radiation exposure [ 38 ]. The same thing has been occurring again after the Fukushima incident [ 39 ]. There are serious concerns about mental health in relation to the Fukushima incident, including stress-related symptoms, and a potentially elevated suicide rate in Fukushima clean-up workers.…”
Section: Risk Communicationmentioning
confidence: 87%
“…40,46,78,89 Control groups were used in 13 studies (16.5%). 16,17,26,30,41,42,48,50,55,62,64,70,71 Most of the studies were based on responses from selfadministered questionnaires (68; 89.4%). Seven studies (9.2%) used medical records retrospectively for their data.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…These rates tended to be higher in control groups that were unaffected by the nuclear disaster. 17,42,48,55,70,71 Only a single study performed a diagnostic interview to measure the prevalence of mental disorders; among the 168 local government workers, the rates for depression and PTSD were 17.9% and 4.8%, respectively. 43 Nishi et al used the government provided statistical data to measure the PD of the residents of the Fukushima prefecture in comparison to the rest of Japan, before and after the disaster.…”
Section: Summary Of the Findingsmentioning
confidence: 99%